Abandoned house - Lev Grigorevich Brodaty:::Creator::::::::::::
Glava Odinndatsataya' (Chapter 11). An Abandoned house.Pen and ink lithograph. Lev Grigorevich Brodaty was born in Warsaw in 1889. A graphic artist, poster artist and illustrator, he created these for a Russian translation (possibly the first) of The Grapes of Wrath. He died in Moscow in 1954.